20x-8=4(4x-9)

Simple and best practice solution for 20x-8=4(4x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20x-8=4(4x-9) equation:


Simplifying
20x + -8 = 4(4x + -9)

Reorder the terms:
-8 + 20x = 4(4x + -9)

Reorder the terms:
-8 + 20x = 4(-9 + 4x)
-8 + 20x = (-9 * 4 + 4x * 4)
-8 + 20x = (-36 + 16x)

Solving
-8 + 20x = -36 + 16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16x' to each side of the equation.
-8 + 20x + -16x = -36 + 16x + -16x

Combine like terms: 20x + -16x = 4x
-8 + 4x = -36 + 16x + -16x

Combine like terms: 16x + -16x = 0
-8 + 4x = -36 + 0
-8 + 4x = -36

Add '8' to each side of the equation.
-8 + 8 + 4x = -36 + 8

Combine like terms: -8 + 8 = 0
0 + 4x = -36 + 8
4x = -36 + 8

Combine like terms: -36 + 8 = -28
4x = -28

Divide each side by '4'.
x = -7

Simplifying
x = -7

See similar equations:

| 4+4y=-20 | | 2x+7=1-4x | | 21/8*4/9 | | 2-3x=4x+17 | | 5=10-x | | 2.6x=-12.532 | | h-1/6h+3(2h^2+9h+4) | | 5.3x+2=12.7x-2 | | 7/8z=1/4 | | h-1/6h+3*(2h^2+9h+4) | | 3(x-2)+3(2x+2)=-3(2-x) | | 4p+3=2p+5 | | 5/9y=-35/81 | | 8(y-2)=4y-32 | | A/5+8=5 | | 8x^2-17x+2=0 | | 3x^2+6x+77=0 | | 9x-z(7x-1)=2 | | 3.2x+6.57=-21.91 | | -2*-2.5-4=1.5*-2.5+7 | | Y/9-2=5 | | 5x-7y=16fory | | X-5.5=4.5 | | X+5.2=3 | | 9^2n=1/6561 | | s+2=7 | | 6+20/a-4=5a/a-4 | | 9^2n1/6561 | | m/4=-14 | | X-47=18 | | 5x^2-30x+12=0 | | 5x+x^2=180 |

Equations solver categories